Ethnobotanical study of medicinal plants used in an urban community in Iloilo City, Philippines - CECILIA S. CORDERO; LANDER R. GUILLERGAN; MARIE FRANCES J. NIEVALES; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2025)
Abstract. Cordero CS, Guillergan LR, Nievales MFJ, Alejandro GJD. 2025. Ethnobotanical study of medicinal plants used in an urban community in Iloilo City, Philippines. Biodiversitas 26: 1940-1954. The use of medicinal plants for treating health problems remains prevalent, even in urban areas where modern medicine is readily available. However, anthropogenic interference may lead in the permanent loss of this knowledge. Therefore, this study aims to document the medicinal plants used in an urban community in Iloilo City, Philippines. A total of 60 participants were selected through convenience sampling and engaged in semi-structured and informal interviews conducted from December 2023 to January 2024. To evaluate the significance of the plants, the Use Value (UV), Relative Frequency of Citation (RFC), and Fidelity Level (FL) were calculated. Fifty-five medicinal plant species, representing 53 genera and 34 families, were recorded as treatments for 36 diseases across 13 different disease categories. Leaves were the most commonly used plant part, with the preferred methods of preparation and application including drinking or bathing the decoction and pounding the leaves to extract the juice for direct application. Ninety percent of all documented plants were either not assessed or listed as least concern on the IUCN Red List, and most of them are non-native to the Philippines. Blumea balsamifera had the highest UV (0.683), Moringa oleifera had the highest RFC (0.650), and Pithecellobium dulce (Roxb.) Benth., Ocimum sp., and Tamarindus indica all tied for the highest FL (100%). Overall, this study emphasized the importance of medicinal plants in disease treatment and could serve as a foundation for future pharmacological research into drug development and formulation. Additionally, it raises awareness of the potential role of plants in healthcare systems.